Thermodynamics : a dynamical systems approach - Haddad, Wassim M., 1961- (Princeton University Press, 2005)
This book places thermodynamics on a system-theoretic foundation so as to harmonize it with classical mechanics. Using the highest standards of exposition and rigor, the authors develop a novel formulation of thermodynamics that can be viewed as a moderate-sized system theory as compared to statistical thermodynamics. This middle-ground theory involves deterministic large-scale dynamical system models that bridge the gap between classical and statistical thermodynamics. The authors' theory is motivated by the fact that a discipline as cardinal as thermodynamics--entrusted with some of the most.
Keywords: Thermodynamics -- Mathematics.; Differentiable dynamical systems.; elektronické knihy; electronic books